Strategies for Engendering Health and Safety Culture in Construction Firms in Abuja, Nigeria - Jimoh, Richard; Oyewobi, Luqman; Uthman, Najeem; Ibrahim, Kabir; Salawu, Ahmed (Journal of Science and Technology, 2020)
Many countries have put in place policies and legislation to reduce accidents and diseases on construction sites though having varied degree of comprehensiveness, the extent of implementation, will and capacity of enforcement. In spite of these efforts, it has been revealed that the increase in the rate of unsafe acts and rate of fatalities in the construction industry is significant due to poor safety culture. Hence, this study assessed the level of health and safety (H&S) culture in construction firms in Abuja by self-administering a total of 152 questionnaires on H&S issues to construction professionals. It included Builders, Quantity Surveyors, Architects, Civil Engineers, and Project Managers/supervisors who were involved in construction works. The data obtained were analysed using percentages and mean scores. It was discovered that despite the increasing growth in the construction firms in Nigeria, the H&S culture practice in construction firms is highly fragmented and poorly implemented. It is recommended among others that there should be high commitment from the top of organisations which will in turn produce higher level of motivation and commitment throughout the organisations.